High-quality development of sports competition performance industry in Chengdu-Chongqing region based on performance evaluation theory - Qiaoyan Yu; Yun Yu; Chenliang Deng; Jinyu Wang (Economics: The Open-Access, Open-Assessment Journal, 2024)
High-quality development of sports competition performance industry in the Chengdu-Chongqing region is based on the improvement of the sports event system and the strengthening of market entities, and it promotes economic and social development by extending the industrial chain and enhancing the value chain. To effectively evaluate its development effect and promote high-quality development, based on the analysis of the opportunities and challenges faced by the sports competition performance industry in the Chengdu-Chongqing region, this article uses the literature research method and survey interview method to construct a performance evaluation index system from the perspective of performance evaluation theory. It also analyzes the strategic thinking of high-quality development from three aspects: guiding ideology, main principles, and development goals, and explores the strategic path for high-quality development from five aspects: integrated development of points and surfaces, priority development between regions, conditional step-by-step development within the region, selective key development of small cities, and layered development with emphasis on different stages.
Keywords: 330; performance evaluation; sports competition performance industry; industrial cluster; high-quality development; Chengdu-Chongqing dual-city economic circle